Effectiveness and Complications of Surgical Drainage in Pediatric Surgery: A Literature Review - Lampus, Harsali; Candy, Candy; Saumur, Odwin B. (Medical Scope Journal, 2026)
Abstract: The use of surgical drainage is a common adjunctive procedure in various pediatric surgeries. However, its effectiveness and associated risks remain a subject of debate, particularly due to variations in drain types, surgical techniques, and the unique characteristics of pediatric patients. This study aimed to evaluate the effectiveness and complications of surgical drainage in various pediatric surgical procedures based on the most recent literature. This narrative literature review was compiled from articles published in the last 10 years (2015–2025), sourced from reputable databases such as PubMed, Cochrane, EBSCO, and Google Scholar. Inclusion criteria encompassed studies involving pediatric patients aged 0–18 years undergoing thoracic, abdominal, ocular, or spinal surgeries, addressing the use of surgical drainage either as a primary intervention or in comparison to non-drain approaches. A total of 20 studies were analyzed in this review. Overall, drainage proved most effective in thoracic and ocular surgeries. In thoracic surgery, devices such as the Thopaz digital drain shortened hospital stays, accelerated recovery, and reduced the number of postoperative radiographs. In ocular surgery, glaucoma drainage devices (GDD) effectively controlled intraocular pressure (IOP) and reduced the need for re-intervention. Conversely, in abdominal surgeries such as appendectomy and laparoscopic pyeloplasty, as well as spinal surgeries, drainage did not confer significant clinical benefits in reducing complications or accelerating recovery. Complications in thoracic surgery included minimal risks such as prolonged air leaks and empyema; in ocular surgery, hypotony, bleb encapsulation, infection, and tube revision were most common; in abdominal surgery, complications included infection, intra-abdominal abscess, bowel obstruction, iatrogenic leaks, peritonitis, and hernia; while in spinal surgery, complications consisted of superficial infections, wound dehiscence, neurological deficits, and hematoma. In conclusion, surgical drainage is most effective in thoracic and ocular surgeries in terms of success rate, accelerated recovery, and reduced length of hospital stay. However, in abdominal and spinal surgeries, drainage offers no significant clinical benefit and carries potential risks of complications. Keywords: surgical drainage; complications; effectiveness; pediatric surgery